Histograms Obtained From Computerized Radiocarbon Age Calibration. Issue 3 (18th July 2016) - Stuiver, Minze; Reimer, Paula
Abstract : Two methods of assigning probability values to calendar years are compared by summing distributions for a large number of 14 C ages derived from samples initially distributed uniformly in calendar years. The radiocarbon ages are calibrated with both a hypothetical calibration curve and the internationally accepted one. The effect of the calibration curve on an ideal and a random sample population is examined.